Development of technical skills in Electrical Power Engineering students: A case study of Power Electronics as a Key Course - Hussain I.S.; Hamid F.A. (Institute of Physics Publishing, 2023)
Curricula; E-learning; Education; Power electronics; Analysis method; Electrical power engineering; Engineering accreditation; Formative and summative assessments; Outcome-based education; Power electronics course; Student levels; Technical skills; Students